Pengaruh Dividend Yield, Earnings Per Share dan Profitabilitas Terhadap Return Saham Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016 - 2020 - Lukman Hakim Rachmawan; Haryati Setyorini (Formosa Journal of Sustainable Research, 2022)
This study aims to examine how the effect of dividend yield, earnings per share, and profitability as proxied by return on assets on stock returns of pharmaceutical companies listed on the Indonesia Stock Exchange. The sample used in this study were 8 pharmaceutical companies that have been listed on the Indonesia Stock Exchange from 2016 – 2020 with the sample selection method using the purposive sampling method. The data used are the company's annual financial statements that have been published on IDX and the data analysis technique is multiple linear regression analysis using the SPSS 16. The results show that simultaneously dividend yield, earnings per share and return on assets have a significant effect on stock returns, partially dividends yield has a significant negative effect on returns, Earnings per Share has a significant positive effect on stock returns, and Return on Assets has a significant positive effect on stock returns.